How to define chronic pruritus: Symptom or disease?. Issue 12 (11th June 2019) - Ständer, Sonja
Abstract: Chronic pruritus (CP) is defined by itching lasting 6 weeks or more and is known to be both a highly prevalent and burdensome symptom of many pruritogenic diseases. Its status as a symptom has many implications mainly that the symptom should evolve and subside with the disease. However, according to the clinical experience, CP often does not parallel the disease course and requires an own management. It is speculated that neuronal sensitization processes take place, which lead to disconnection of the symptom from the underlying disease and establishment of an own course of pruritus. It is thus discussed that pruritus can be both a symptom of diseases and an entity by itself. Further studies are needed to learn more and improve our understanding of this condition. This article compares its role in pruritogenic diseases, encourages discussion on the topic and provides an overview of the proper questions to ask.